Efficacy testing of antimicrobial peptides against bacteria. - Sim, Huay Ping. (2009)
This project aims to evaluate the efficacies of a short synthesized antimicrobial peptide against common ocular pathogens. The proposed antimicrobial peptide could serve as a promising ingredient in numerous applications, especially in contact lens storage and washing solutions. The engineered antimicrobial peptide consists of 25 amino acid nucleotides comprised of 40% lysine residues and 60% phenylalanine residues. In this report, the physical and biophysical properties of antimicrobial peptides were explored, together with their antimicrobial mechanisms on pathogens and the mechanisms of pathogen resistance to the antimicrobial peptides. Susceptibility methods to determine the minimum inhibitory concentration of the antimicrobial peptide and killing assay of antimicrobial peptides against pathogens were discussed. For a deeper understanding, atomic force microscopy was employed to scrutinize the morphology of the pathogens after being subjected to the antimicrobial peptide. Steps to determine membrane depolarization of pathogens after interaction with the antimicrobial peptide were proposed as well. The experimental results provided evidence that the short engineered peptide was able to decrease viability of pathogens and cause drastic morphological changes, hence demonstrating their ability in effectively eliminating pathogens. Its prospect and relevance in being an effective antimicrobial agent in contact lenses storage and washing solution was thus reinforced. Future directions and recommendations were included in this report.